The relationship between core strength with static and dynamic balance in snowboard skiing male athletes - Seyedeh Samin Razavi; Ali Asghar Norasteh; Maryam Banparvari (Vesnu Publications, 2014)
Introduction: Ski is a fast sport with a high risk of falling. The purpose of this study is to investigate the relationship of core strength with static and dynamic balance in snowboarders. Materials and Methods: forty male athletes participated in this study with a history activity of at least 6 seasons in snowboard skiing sport (mean age 26.85±3.30yr, height 180.45±6.08cm, weight 79.86±6.14kg and athletic experience 12.70±4.53season). Subjects were selected  by available sampling. Core strength has been measure by Nicholas hand held dynamometer. also static and dynamic balance has been  measure by stork and star excursion balance tests. Windows Vista SPSS18 software was used for data analysis. Data were analyzed using by Pearson correlation test (P˂0.05). Results: Results indicated that there was significant relationship between core strength with static balance (P= 0.001) and dynamic balance (P= 0.001). Conclusion: Considering the present study's results significant relationship between core strength with static and dynamic balance in snowboard skiing athletes and also importance balance in this sport, researcher find out strengthening core musculature training program can positively affect balance and  prevent injuries in snowboarders. Keywords: Hip Isometric Strength, Static Balance, Dynamic Balance, Snowboarders.